Practical guidelines for radiographers to improve computed radiography image quality - Napapong Pongnapang (2018)
Computed Radiography (CR) has become a major digital imaging modality in a modern radiological department. CR system changes workflow from the conventional way of using film/screen by employing photostimulable phosphor plate technology. This results in the changing perspectives of technical, artefacts and quality control issues in radiology departments. Guidelines for better image quality in digital medical enterprise include professional guidelines for users and the quality control programme specifically designed to serve the best quality of clinical images. Radiographers who understand technological shift of the CR from conventional method can employ optimization of CR images. Proper anatomic collimation and exposure techniques for each radiographic projection are crucial steps in producing quality digital images. Matching image processing with specific anatomy is also important factor that radiographers should realise. Successful shift from conventional to fully digitised radiology department requires skilful radiographers who utilise the technology and a successful quality control program from teamwork in the department. © 2005 Biomedical Imaging and Intervention Journal. All rights reserved.